MODERN JUDICIAL EXPERTOLOGY – THE SCIENCE OF FORENSICS AND FORENSIC ACTIVITIES - E. R. Rossinskaya (Теория и практика судебной экспертизы)
The history and objective prerequisites for the formation the theory of forensic science in the 80s - 90s of the last century as an interdisciplinary theory are examined It is noted that the role of expertise in legal proceedings, the theory and practice of forensic science in the XXI century, necessitates the formation on the basis of interdisciplinary science theory full - judicial expertology. The author oﬀers a deﬁnition of the subject of judicial expertology, based on the basic laws studied this science, as well as the system of science.